2000
DOI: 10.1111/j.1469-445x.2000.02050.x
|View full text |Cite
|
Sign up to set email alerts
|

Ageing Modulates some Aspects of the Non‐Specific Immune Response of Murine Macrophages and Lymphocytes

Abstract: The deterioration of the immune system with ageing, which leads to an increased morbidity and mortality from infections, appears to be related to decreases in specific lymphocyte functions. However, the alteration of non-specific immunity is a more controversial subject. Our purpose was to investigate the age-related changes of different functions of the non-specific immune response in peritoneal macrophages (adherence to tissues, mobility directed to a chemical gradient from an infectious focus or chemotaxis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…The migration ability is another important property of lymphocytes, crucial for their accumulation at sites of injury or inflammation. In previous studies, we have found that lymphocyte is lower in aged compared with adult subjects, 6,36 a fact observed in the PAM groups compared with the NPAM groups in the present study. Previous reports have shown that, under conditions of oxidative stress, such as endotoxic shock, 37 or in states with deficient levels of anti‐oxidants, 31 there is lower chemotaxis.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The migration ability is another important property of lymphocytes, crucial for their accumulation at sites of injury or inflammation. In previous studies, we have found that lymphocyte is lower in aged compared with adult subjects, 6,36 a fact observed in the PAM groups compared with the NPAM groups in the present study. Previous reports have shown that, under conditions of oxidative stress, such as endotoxic shock, 37 or in states with deficient levels of anti‐oxidants, 31 there is lower chemotaxis.…”
Section: Discussionsupporting
confidence: 75%
“…In the immune system, the functional state of which is a very good marker of health and longevity, 1,2 the anti‐oxidant–oxidant balance is an important determinant of immune cell function, including the maintenance of the integrity and functionality of membrane lipids, cellular proteins and nucleic acids and the control of the signal transduction of gene expression 3 . A gradual decline in the functionality of the immune system has been described with advancing age, 4–7 the T lymphocyte being the most severely affected immune cell, 8,9 although some age‐associated changes also occurs in components of innate immunity 10–12 . For these reasons, anti‐oxidant deficiencies are commonly associated with an impaired immune response, particularly cell‐mediated immunity, which leads to frequent severe infections resulting in increased mortality 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the T cell compartment, i.e., [ 41 , 45 ], the effects of ageing on professional APC such as B cells, monocytes/macrophages, and dendritic cells (DC) have received much less attention. There is evidence that monocytes and macrophages from aged mice have a reduced functional potential [ 46 , 47 ]. Very little is known about DC changes with age, although their number in the epidermis decreases with age [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conflicting results have been reported on the agedependent changes of monocyte/macrophage functional capacities. In detail, while the features of adherence and chemotaxis are increased in old thymus (Ortega et al 2000), there are several results showing a different phagocytic capacity in old macrophages. Some authors, in fact, showed that this capacity is diminished or unchanged in age subjects, while others have found an increased phagocytic activity of these cells during old age (Ortega et al 2000).…”
Section: Aging and Macrophagesmentioning
confidence: 98%